Relation Between Parents’ Education and Residence with Knowledge and Attitude on Children Oral Health - Yulie Emilda; Istien Wardani; Eriza juniar; Catherine Ivanna Edward (Denta Journal Kedokteran Gigi, 2023)
Background: Parents’ knowledge and attitude on children oral health will form their childrens’ underlying behaviour which will either support or not their children’s oral health. Objective: To know whether there parents’ level of education and residence (coastal vs urban areas) are related with  their knowledge and attitude regarding the oral health of children age 3-6 years old. Materials and Methods: This research is a cross  sectional study using survey. The samples that were studied were 41 parents of 3-6 years old children in PG/ TK Benih Kasih Surabaya and 41 parents of 3-6 years old children in TK/ PAUD Benih Prima Batam. The method of collecting data is by non-experimental survey. Statistical analysis on the relationship between variable was performed using Spearman Rank Correlation. Results: The research showed that level of education has a positive relationship with knowledge and this relationship goes both ways. Level of education also has positive relationship with attitude and vice versa. On the other hand, residence has insignificant relationship with knowledge. Meanwhile, residence has negative relationship with attitude. Conclusion: The higher the level of education of parents relates to higher level of knowledge and attitude regarding the oral health of children and vice versa. Meanwhile the residence, whether coastal area of Batam or urban area of Surabaya, has no relationship with the knowledge. Parents in urban area of Surabaya, on the other hand, has significant relationship with positive attitude toward children’s oral health, and this relationship goes both ways.